2013
DOI: 10.1080/09712119.2012.738227
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin condensation and morphometry of the bovine sperm head afterin vitrosperm selection and capacitation

Abstract: Methods of sperm selection and concentration are used to improve efficiency in obtaining viable embryos from in vitro fertilization procedures. Eighteen semen samples were submitted for selection with Percoll gradient and swim-up methods, followed by in vitro sperm capacitation with heparin, to assess the effect of selection method on chromatin condensation and sperm head morphometry. Smears were made at each stage of the process and stained with toluidine blue (TB). Digital images were analysed using computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 28 publications
3
5
0
6
Order By: Relevance
“…Such chromatin decondensation should be moderate, because, beyond certain levels, a high or null chromatin condensation could compromise the fertilizing potential of spermatozoa 15,17,24 . In line with previous studies conducted in bull and human sperm, 22‐24 our results for AB revealed that sperm chromatin condensation decreased during in vitro capacitation of ram spermatozoa. This variation in the chromatin condensation level was initiated in cryopreserved ram spermatozoa earlier than in fresh, reaching the highest percentages of spermatozoa with decondensed chromatin (AB+) at 5‐30 minutes in cryopreserved samples and at 180‐240 minutes in fresh samples.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Such chromatin decondensation should be moderate, because, beyond certain levels, a high or null chromatin condensation could compromise the fertilizing potential of spermatozoa 15,17,24 . In line with previous studies conducted in bull and human sperm, 22‐24 our results for AB revealed that sperm chromatin condensation decreased during in vitro capacitation of ram spermatozoa. This variation in the chromatin condensation level was initiated in cryopreserved ram spermatozoa earlier than in fresh, reaching the highest percentages of spermatozoa with decondensed chromatin (AB+) at 5‐30 minutes in cryopreserved samples and at 180‐240 minutes in fresh samples.…”
Section: Discussionsupporting
confidence: 89%
“…Some authors have investigated whether the acquisition of sperm fertilizing ability through the physiological process known as capacitation 19,20 might prepare the sperm chromatin for optimal remodelling after oocyte penetration. In boar spermatozoa, a reduction in disulphide bonds between protamines was observed under capacitating conditions, 21 while in bull and human spermatozoa, the degree of chromatin condensation decreased during in vitro capacitation without affecting DNA integrity 22‐24 . Such changes in nuclear compaction could facilitate the events surrounding and following fertilization, as has been suggested by De Lamirande et al 22 In line with these findings, Pérez‐Cerezales et al 25 demonstrated that a specific subpopulation of capacitated spermatozoa was selected by in vitro thermotaxis in humans and mice.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…O Azul de toluidina (AT), é outro método utilizado para identificar alterações da cromatina e que permite avaliação concomitante da morfometria espermática (BELETTI, COSTA, 2003;BELETTI, MELLO, 2004, BELETTI et al, 2005 (BELETTI, MELO., 2004;NAVES et al, 2004;BELETTI et al, 2005;SILVA et al, 2008;RODRIGUES et al, 2009;OLIVEIRA et al, 2011;KANAYAMA;BELETTI, 2011;CAMPOS et al, 2013;SOUZA et al, 2018) O uso de análise de imagem assistida por computador é importante, pois elimina a subjetividade inerente a outros métodos, além de permitir um estudo detalhado das alterações da cromatina, ajudando a identificá-las e classificá-las de acordo com a localização (SOUZA et al, 2018).…”
Section: Azul De Toluidinaunclassified
“…Fourier 2 representa a elongação da cabeça do espermatozoide(BARTH,1989). Simetria lateral identifica a simetria ao longo da cabeça do espermatozoide, pode ser utilizada como um indicativo da hidrodinâmica do espermatozoide(GAMA-CAMPOS et al, 2013). Simetria ântero-posterior analisa o eixo secundário da cabeça do espermatozoide, influencia também na hidrodinâmica.…”
unclassified